Transplanted neocortical neurons migrate selectively into regions of neuronal degeneration produced by chromophore-targeted laser photolysis - Macklis, JD (J Neurosci, 1993)
Selective degeneration of neocortical callosal pyramidal neurons by noninvasive laser illumination was used for directed studies of neocortical transplantation, to test the hypothesis that transplanted embryonic neurons may seek to restore normal cytoarchitecture within an appropriately permissive local environment. At long wavelengths that penetrate through tissue without major absorption, photolysis can cause extremely selective degeneration to desired subpopulations of targeted neurons in vivo (Macklis and Madison, 1991; Madison and Macklis, 1993). Cell death is geographically defined and slowly progressive, allowing control over the anatomical substrate for transplantation. Targeting occurs by retrograde incorporation of cytolytic chromophores that are activated by specific-wavelength light. Intermixed neurons, glia, axons, blood vessels, and connective tissue remain intact. Degeneration was effected within neocortical lamina II/III of neonatal mouse pups following targeting in utero or early postnatally with photoactive nanospheres. Total neuron density was reduced typically by 25–30% within defined areas, with approximately 60% loss of large projection neurons and no change in the number of small, presumptive interneurons. Embryonic day 17 neocortical cell suspensions, which included recently postmitotic neurons destined to form lamina II/III, were transplanted lateral to these regions of ongoing neuron degeneration in juvenile mice. Cellular injections spanned laminae II-V, to provide donor neurons with both lateral and laminar choice for possible migration and integration. Donor cells were labeled in vitro with unique fluorescent and electron-dense nanospheres that allowed distinct identification of donor cells at both light and electron microscopic levels. Control experiments included neocortical transplants into intact age-matched hosts, into hosts with kainic acid lesions to neocortex, or distant to the region of photolytic neuronal degeneration; embryonic cerebellar transplants to the regions of selective photolytic degeneration; and grafts of hypoosmotically lysed neocortical cells to lesioned regions. After survival times of 1 hr to 12 weeks, labeled neurons were identified morphologically and positions were digitized for qualitative and quantitative analysis of position and specificity of migration and cellular integration; electron microscopy was used to confirm further the donor identities of migrated neurons. Neurons placed near host zones of photolytic neuron degeneration migrated up to 780 microns specifically within these zones; approximately 44% of donor neurons migrated significantly beyond the injection site to enter these regions. Migration and integration did not occur in normal, unaffected deeper layers IV-VI of these experimental mice, or in the normal lamina II/III bordering the transplantation site on the side opposite the neuron-deficient region. Control grafts of all five types revealed only minimal local spread without laminar preference.(ABSTRACT TRUNCATED AT 400 WORDS)